Acute Abdominal Pain in Childhood, with Special Reference to Cases not due to Acute Appendicitis. Issue 5639 (1st February 1969) - Jones, Peter F.
Abstract : Appendicitis is not the only common cause of acute abdominal pain in childhood. Almost equally common is an acute episode which in its early stages resembles acute appendicitis but which subsides without treatment in 24 to 48 hours. The clinical features of this syndrome are contrasted with those of appendicitis. The two conditions cannot always be distinguished on clinical grounds, leading to admission to hospital for observation and the finding of a normal appendix in 14% of operations for suspected appendicitis. Reasons are given for abandoning attempts to diagnose acute mesenteric adenitis at the bedside.